Support from Physicians as a Key Enabling Factor for Rehabilitation Utilization in Migrants with Back Pain: A Longitudinal Analysis - Hannes Banaschak; David Fauser; Annika Sternberg; Julia-Marie Zimmer; André Golla; Wilfried Mau; Matthias Bethge (Journal of International Migration and Integration, 2024)
Abstract In Germany, medical rehabilitation is provided to promote work ability and health in the case of chronic illness and to avoid early disability pensions. Studies have shown that employees with a history of migration are less likely to seek medical rehabilitation. The aim of this paper was to examine which factors influence the use of medical rehabilitation services in migrants with back pain. We used data from a German cohort study also including migrant employees aged 45 to 59 years. Participants reported back pain in the last 3 months and completed a baseline questionnaire in 2017. Data on rehabilitation utilization was extracted from administrative records covering the period until the end of 2018. Proportional hazard models were fitted to identify factors that were associated with utilized rehabilitation measures. Data of 552 participants were included, and 25 individuals utilized rehabilitation during follow-up. Sex (women: HR0.167em=0.167em3.05; 95% CI: 1.10; 8.45), higher job insecurity (HR0.167em=0.167em1.02; 95% CI: 1.00; 1.03), support from physicians and therapists (HR0.167em=0.167em2.22; 95% CI: 1.52; 3.24), proportion of foreigners (HR0.167em=0.167em3.27; 1.17; 9.15), and the self-reported need for rehabilitation (HR0.167em=0.167em3.23; 95% CI: 1.12; 8.60) were associated with utilization. In summary, informational and practical support provided by physicians and therapists on medical rehabilitation services seems to be a key predictor of rehabilitation utilization. Our findings, therefore, support the call for transcultural competence to be more widely incorporated into the education of medical and health professionals to counteract health care disparities.
Keywords: 330; Health care inequalities; Rehabilitation; Human migration; Back pain; Utilization; Health services use; Transcultural competence